Repurposing of monacolin K decorated BN nanoparticle on inhibition of HMG-CoA reductase: In silico approach - Vahid Khori; Mahdi Zahedi; Hassan Mirzaei; Ali Jabbari; seyedbabak Mojaveraghili; Seyed Ghadir Hosseini (Chemical Physics Impact, 2023)
To identify a novel inhibitor of 3‑hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase, the current perspective has shifted toward a B12N12 nanocage that also has cardioprotective properties. Therefore, this study identified the bioactive complexes derived from monacolin K and BN nanoparticle and determines their potential for inhibiting HMG-CoA reductase, hypolipidemic activity, and anti-apoptotic properties via molecular docking. A molecular docking study was conducted with the Auto Dock Vina software on a complex of monacolin K and the B12N12 fullerene using an in silico docking approach. The protein structures of selective HMG-COA reductase, as well as peroxisome proliferator-activated receptor-α (PPAR-α) and others, were obtained from Protein Data Bank (PDB). The binding affinity between key residues involved in the binding mode of the targets and selective complexes is identified via in silico molecular docking. A further evaluation of the ADMET properties of the selective complexes has also been carried out. B12N12 nanoparticles and monacolin K complex (A) showed higher inhibitory potential for HMG-CoA reductase than monacolin K alone. These complexes seemed to be selective to the PPAR-α and caspase3 domains. Meanwhile, complex B had the highest binding affinity to the active site of SGK, TNF- α, NF-Kβ and AMPK receptors. Furthermore, both complex A and B could inhibit inflammatory targets more efficiently. The selective B12N12 nanoparticles were assessed for their drug-likeness and ADMET analysis, confirming that the selective B12N12 nanoparticles met the Lipinski and drug-likeness criteria. It was revealed that B12N12 fullerene and monacolin K complexes have potential inhibitory HMG-COA reductase and anti-apoptotic properties, as well as activating PPAR-α and AMPK. Consequently, these cardioprotective effects lead to improved cardiovascular health.